2023
DOI: 10.1037/cpb0000241
|View full text |Cite
|
Sign up to set email alerts
|

Race matters in coaching: An empirical study of coaches’ willingness to have difficult conversations with leaders of color.

Abstract: Do executive coaches have the skill sets necessary for effective partnership with Black leaders? Such inquiry remains unexamined, yet research from similar disciplines—such as education, medicine, and counseling—casts doubt. Drawing on these findings, a between-subjects experiment sampled 105 White coaches in the United States and examined their willingness to have “difficult conversations” with Black clients. The study investigated two questions in particular: (a) Do coaches provide less critical feedback to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 95 publications
(111 reference statements)
0
8
0
Order By: Relevance
“…Knowing how these factors influence the initiation of coaching seems especially important. For example, Bernstein (2023) reported that coaches might "sidestep" cross-racial conversations or withhold feedback or criticism depending on their coachees' race or ethnicity. Yet, the present study challenges this assertion and suggests that once the rapport between the coach and coachee is established concerns related to gender and race could become less pronounced.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Knowing how these factors influence the initiation of coaching seems especially important. For example, Bernstein (2023) reported that coaches might "sidestep" cross-racial conversations or withhold feedback or criticism depending on their coachees' race or ethnicity. Yet, the present study challenges this assertion and suggests that once the rapport between the coach and coachee is established concerns related to gender and race could become less pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have considered specific coaching behaviors (Gessnitzer and Kauffeld, 2015), a given coach's skills (Baron and Morin, 2009), power dynamics (Welman and Bachkirova, 2010) and the structure of the coaching session (Sonesh et al, 2015) as important predictors of coaching outcomes. More recently, scholars have investigated whether differences in race or ethnicity influence coaching practice (Bernstein, 2023). Bernstein's (2023) study reported that coaches tend to "sidestep cross-racial conversations that centered on diversity and development" (p. 32).…”
Section: Conceptualizing the Factors That Could Influence Initiation ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The BIPOC coaches' testimonies suggest that an antiracist approach oriented toward decoloniality could be much more effective in breaking down patterns of underrepresentation and exclusion at senior leadership levels across organizations. Bernstein (2023) looked at two critical questions related to coaching efficacy in cross-racial coaching relationships: (a) the provision of critical feedback and (b) engagement in diversity-based conversations. Their qualitative research found that White coaches provided more support in their coaching efforts rather than critical feedback (challenges or constructive feedback) to Black coachees compared to their White counterparts.…”
mentioning
confidence: 99%